An adolescent girl with Rapunzel syndrome: Case report with review of literature - Pradnya M Diggikar; Prasanna K Satpathy; Arjun L Kakrani; Mukesh Laddha (Medical Journal of Dr. D.Y. Patil University, 2013)
Trichobezoar is a collection of dense mass of hair in stomach. When this extends into any part of the small intestine it is called Rapunzel Syndrome (RS). We report here, a case of RS in an adolescent girl who had presented with epigastric pain and swelling. Gastroscopy confirmed the presence of trichobezoar. She underwent gastrotomy and a large dense mass of hair extending up to first part of duodenum was removed. Her parents revealed their daughter′s impulsive nature of scalp-hair pulling. Following surgery, Psychiatric consultation was sought to prevent recurrence. Trichobezoar is a very rare cause of upper abdominal mass and should be considered if there is a very strong history of impulsive hair pulling. Surgical removal of a large trichobezoar is the only treatment of cure and psychiatric treatment that prevents its recurrence.